Aluminum-niobium co-doped lithium-rich layered positive electrode material and preparation method thereof
Through aluminum-niobium co-doping and electrospinning technology, lithium-rich layered cathode material with excellent cycling stability and rate performance was prepared, solving the problem of fast voltage and capacity decay during the cycle of existing materials, and achieving high energy density and long-life battery performance.
Patent Information
- Application Number
- CN202411595453.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing lithium-rich layered cathode materials have problems such as fast voltage and capacity decay and poor rate performance during the cycle process, which are mainly due to the oxidation of oxygen ions and the migration of manganese ions in the transition metal layer, resulting in crystal structure transformation and low electron conductivity.
Through aluminum-niobium co-doping technology, a cationic colloid solution of Li1.2-xAlx (Mn0.54Ni0.13Co0.13)0.8-yNbyO2 chemical formula was prepared. Lithium ion and niobium salt powder were added during the spinning process by electrospinning technology to form a porous structure and a uniform conductive coating layer to improve the cyclic stability and rate performance of the material.
The discharge specific capacity and rate performance of the positive electrode material are significantly improved, and excellent cycling stability is obtained, capacity attenuation is reduced, and the energy density of the battery is improved.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of lithium ion battery electrode materials, and in particular to an aluminum-niobium co-doped lithium-rich layered positive electrode material and a preparation method thereof. Background Art
[0002] With the proposal of the "carbon neutrality and carbon peak" goals, reducing greenhouse gas emissions has become a hot topic of social development. Cars powered by gasoline and diesel combustion are the main source of carbon emissions in the transportation sector. Therefore, the development of green and zero-carbon dioxide emission new energy vehicles has become a global consensus. At present, the cruising range of new energy vehicles still cannot meet the requirements. The key material that restricts the cruising range of power batteries lies in the positive electrode material. Commercial positive electrode materials mainly include lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate and ternary positive electrode materials. However, these materials have low discharge specific capacity and operating voltage, and cannot meet the requirements of high energy density commercial positive electrode materials.
[0003] The discharge capacity of lithium-rich layered materials is higher than 250 mAh g -1 , the operating voltage range is 2.0-4.8V, and its energy density is higher than 1000Whkg -1 , which is expected to become the positive electrode material of the next generation of commercial power batteries. However, due to the limitations of its own crystal structure, the lithium-rich layered material has the following problems: fast voltage and capacity decay and poor rate performance. Studies have shown that the main reason for the fast voltage and capacity decay is that the oxygen ions are oxidized to generate oxygen during the first cycle, and the manganese ions in the transition metal layer migrate, and then the crystal structure of the material changes from layered structure to spinel structure during the material cycle; the main reason for the poor rate performance is that there are a lot of Mn 4+ , which makes the electronic conductivity of the material lower and reduces the rate of electron transfer under large current. In order to solve the above problems, a common method is to improve the local crystal structure and electronic structure of the material by element doping, thereby improving the cycle performance and rate performance of lithium-rich layered materials.
[0004] Aluminum has been widely used as a doping element in lithium-ion battery positive electrode materials. Since the Al-O bond energy is stronger than the TM-O bond energy (TM is one of Ni, Co and Mn), doping Al into the transition metal ion site can improve the crystal structure stability of the positive electrode material, thereby improving the cycle performance. Although aluminum can improve the structural stability of the positive electrode material, since it does not participate in the embedding and de-embedding of lithium ions, aluminum doping will occupy active sites and reduce the space in the material that can accommodate lithium ions, which will lead to a decrease in the specific capacity of the material. In other words, the lithium ions stored per unit weight of the material are reduced, thereby affecting the energy density of the battery and the discharge specific capacity of the battery. Summary of the invention
[0005] To solve the above technical deficiencies, the present invention has developed an aluminum-niobium co-doped lithium-rich layered cathode material and its preparation method, which not only greatly improves the discharge specific capacity of the prepared cathode material, obtains excellent rate performance, but also endows it with excellent cycle stability.
[0006] An aluminum-niobium co-doped lithium-rich layered cathode material, characterized in that the chemical general formula of the cathode material is: Li 1.2-x Al x (Mn 0.54 Ni 0.13 Co 0.13 ) 0.8-y Nb y O2, where 0.01 < x < 0.1 and 0.01 < y < 0.1.
[0007] Its preparation method includes the following steps:
[0008] S1: Preparation of cationic colloidal solution
[0009] Mix manganese salt, nickel salt, cobalt salt and aluminum salt evenly and dissolve them in deionized water, then add ethylene glycol and stir evenly to obtain solution A. Mix polyvinylpyrrolidone and absolute ethanol evenly to obtain PVP solution. Slowly drip solution A into the PVP solution while stirring to obtain a spinning solution. Stir diphenyl phosphite, tartaric acid and absolute ethanol evenly to obtain a complexing agent. Mix soluble lithium salt, complexing agent and deionized water evenly to obtain solution B. Spray the spinning solution into an alkaline solution through an electrospinning machine, and slowly add solution B while keeping the pH constant, and continuously heat and stir the alkaline solution during the spinning process to obtain solution C. The ratio of lithium ions, manganese ions, nickel ions, cobalt ions and aluminum ions in solution C is in accordance with the stoichiometric ratio of Li 1.2-x Al x (Mn 0.54 Ni 0.13 Co 0.13 ) 0.8-y Nb y O2, 0.01 < x < 0.1, 0.01 < y < 0.1, and then carry out water bath heating to obtain a cationic colloidal solution;
[0010] S2: Preparation of derivative carbon precursor solution
[0011] After crushing natural shellac and mixing it with hexane, perform constant-temperature ultrasonic treatment, filter and collect the solid to obtain wax-free shellac. Mix the wax-free shellac with absolute ethanol, heat and stir, filter to obtain a shellac extract. Concentrate and evaporate the shellac extract, add deionized water, stir evenly, refrigerate, then perform centrifugal filtration, retain the precipitate and dry it to obtain a shellac extract. Mix the shellac extract, 1,8-naphthalenedicarboxylic anhydride and ethanol, heat and then perform ultrasonic dispersion, and cool to obtain a derivative carbon precursor solution;
[0012] S3: Coating and sintering of the positive electrode powder material
[0013] Place the cationic colloid solution in a container. According to the ratios of lithium ions, manganese ions, nickel ions, cobalt ions and aluminum ions in solution C, add niobium salt powder according to the stoichiometric ratio of Li 1.2-x Al x (Mn 0.54 Ni 0.13 Co 0.13 ) 0.8-y Nb y O2, where 0.01 < x < 0.1 and 0.01 < y < 0.1. Stir evenly and then dry, then place it in a tube furnace for pre-sintering. After cooling and crushing, obtain sintered powder. Immerse the sintered powder in the derivative carbon precursor solution, stir and then dry the derivative carbon precursor solution to obtain a solid product. Place the solid product in a tube furnace and calcine it under a N2 protective atmosphere to obtain an aluminum-niobium co-doped lithium-rich layered positive electrode material.
[0014] Furthermore, the preparation of the cationic colloid solution in step S1 includes the following steps:
[0015] S1.1: Mix soluble manganese salt, nickel salt, cobalt salt and aluminum salt evenly to obtain a mixed metal salt. The molar ratio of manganese, nickel, cobalt and aluminum elements in the mixed metal salt is 4.15:1:1:(0.1 - 1.1). Dissolve the mixed metal salt in 15 - 20 times the mass of deionized water, then add 4 - 6 times the mass of ethylene glycol of the mixed metal salt, and stir at a speed of 300 - 400 rpm for 20 - 25 minutes to obtain solution A;
[0016] S1.2: Mix polyvinylpyrrolidone and absolute ethanol in a mass ratio of 1:(10 - 12) and place them in a container, then stir at a speed of 600 - 800 rpm for 25 - 30 minutes to obtain a PVP solution. Take 2 - 3 parts of the PVP solution and place it in a container, slowly drip 1 - 1.5 parts of solution A, and stir at a speed of 450 - 500 rpm at the same time. Stop stirring when the addition of solution A is completed to obtain a spinning solution;
[0017] S1.3: Mix diphenyl phosphite, tartaric acid, and absolute ethanol in a mass ratio of 1:(3 - 4):(15 - 20) in a container, stir at a speed of 300 - 500 rpm for 10 - 15 minutes to obtain a complexing agent. Mix soluble lithium salt, the complexing agent, and deionized water in a mass ratio of 1:(10 - 20):(45 - 60) evenly to obtain solution B. Place the alkaline solution in a container, with an electrospinning machine above the container. The syringe of the electrospinning machine is 20 - 30 cm away from the liquid level of the alkaline solution. Place the spinning solution in the syringe of the electrospinning machine. The syringe aperture is 600 - 800 μm. Set the spinning voltage to 8 - 10 kV, the spinning temperature to 30 - 35 °C, and the syringe injection speed to 0.1 - 0.3 mm / min. Then start the electrospinning machine to electrospin the spinning solution and continuously spray it into the alkaline solution. At the same time, slowly add solution B, continuously stir at a speed of 350 - 400 rpm and heat to 55 - 60 °C, keeping the pH of the alkaline solution unchanged. After the electrospinning is completed, obtain solution C. The ratio of lithium ions, manganese ions, nickel ions, cobalt ions, and aluminum ions in solution C is formulated according to the stoichiometric ratio of Li 1.2-x Al x (Mn 0.54 Ni 0.13 Co 0.13 ) 0.8-y Nb y O2, where 0.01 < x < 0.1 and 0.01 < y < 0.1. Then carry out a water bath heating at 80 - 90 °C for 3 - 4 hours to obtain a cationic colloidal solution.
[0018] Further, the preparation of the derivative carbon precursor solution in step S2 includes the following steps:
[0019] S2.1: Crush natural shellac and sieve it through a 40 - 50 - mesh sieve to obtain shellac powder. Mix the shellac powder and hexane in a mass ratio of 1:(25 - 30) in a constant - temperature ultrasonic water bath, adjust the power to 200 - 250 W, the temperature to 40 - 45 °C, carry out ultrasonic treatment for 20 - 30 minutes, and then filter and collect the solid to obtain wax - free shellac;
[0020] S2.2: Mix the wax-removed shellac and absolute ethanol in a mass ratio of 1:(20 - 25) in a container, heat it to 50 - 60 °C, stir at a speed of 400 - 500 rpm for 40 - 45 minutes, then filter to remove insoluble impurities to obtain a shellac extract. Evaporate and concentrate the shellac extract to 1 / 4 - 1 / 3 of the original volume, then add deionized water with the same volume as the reduced volume, stir evenly, place it in a refrigerator at 3 - 4 °C and let it stand for 8 - 10 hours, then centrifuge at a centrifugal speed of 3800 - 4000 rpm for 10 - 15 minutes, filter with suction to retain the precipitate, and then dry it at 45 - 50 °C to obtain a shellac extract;
[0021] S2.3: Place the shellac extract, 1,8-naphthalenedicarboxylic anhydride and ethanol in a mass ratio of 1:(0.1 - 0.2):(8 - 10) in an ultrasonic disperser, heat it to 50 - 55 °C, and then perform ultrasonic dispersion at an ultrasonic frequency of 15 - 20 kHz for 12 - 16 minutes, and cool to room temperature to obtain a derivative carbon precursor solution.
[0022] Further, the coating and sintering of the positive electrode powder material in step S3 includes the following steps:
[0023] S3.1: Place the cationic colloid solution prepared in step S1.3 in a container. According to the ratio of lithium ions, manganese ions, nickel ions, cobalt ions and aluminum ions in solution C in step S1.3, add niobium salt powder according to the stoichiometric ratio of Li 1.2-x Al x (Mn 0.54 Ni 0.13 Co 0.13 ) 0.8-y Nb y O2, where 0.01 < x < 0.1 and 0.01 < y < 0.1. Stir at a speed of 600 - 800 rpm for 20 - 25 minutes, then place it in an oven and dry it at a temperature of 150 - 200 °C for 10 - 12 hours, and then place it in a tubular furnace and pre-sinter it at a temperature of 450 - 500 °C for 6 - 8 hours. After cooling, place it in an ultrafine pulverizer and pulverize it to obtain a sintered powder;
[0024] S3.2: Immerse the sintered powder prepared in step S3.1 in the derivative carbon precursor solution, stir at a speed of 300 - 400 rpm for 15 - 20 minutes, then place it in an oven and dry the derivative carbon precursor solution at a temperature of 75 - 80 °C to obtain a solid product. Fill the solid product into a crucible and place it in a tubular furnace. Under a N2 protective atmosphere, heat it at a heating rate of 3 - 5 °C / min to 750 - 850 °C, and keep the temperature and calcine it for 8 - 10 hours to obtain an aluminum-niobium co-doped lithium-rich layered positive electrode material.
[0025] Furthermore, in step S1.1, the manganese salt is one or more of manganese sulfate, manganese nitrate and manganese chloride; the nickel salt is one or more of nickel sulfate, nickel nitrate and nickel chloride; the cobalt salt is one or more of cobalt sulfate, cobalt nitrate and cobalt acetate; the aluminum salt is one or more of aluminum sulfate, aluminum nitrate and aluminum chloride.
[0026] Furthermore, the soluble lithium salt in step S1.3 is one or both of lithium nitrate and lithium acetate.
[0027] Furthermore, the alkaline solution in step S1.3 is an ammonia solution with a pH of 8.5-9, and the volume is 10-15 times the volume of the subsequent spinning solution.
[0028] Furthermore, the niobium salt powder in step S3.1 is niobium pentachloride powder.
[0029] Furthermore, the particle size of the sintered powder in step S3.1 is 10-20 μm.
[0030] The beneficial effects are as follows: 1. In the present invention, solution A is prepared by mixing manganese salt, nickel salt, cobalt salt, aluminum salt and ethylene glycol, and then slowly dripping the mixture into a PVP solution to prepare a spinning solution. Then, a soluble lithium salt, a complexing agent and deionized water are uniformly mixed to prepare a solution B. The spinning solution is directly sprayed into an alkaline solution by an electrospinning machine, and solution B is added at the same time, and solution B is continuously heated and stirred. The obtained solution C is concentrated in a water bath to obtain a colloidal solution. At the moment when the spinning solution is electrospun into the alkaline solution, a precipitate is generated on the surface of the nanofiber and is quickly fixed, thereby retaining a relatively high nanoscale fiber morphology and having a high specific surface area, which is beneficial to the subsequent preparation of the electrode material for the electrode. The charge transfer and diffusion of lithium ions increase the discharge capacity of the material, and a precipitation reaction occurs inside the fiber through a diffusion mechanism. Since the precipitation reaction is carried out gradually from the outside of the fiber to the inside, the final precursor is not only arranged in an orderly manner, but also has a porous structure, which provides more lithium ion diffusion channels, reduces the ion diffusion resistance, and improves the rate performance of the electrode material. The precipitation reaction is carried out while spinning, which can not only form an interlocking structure between fibers, but also allow the added lithium ions to be deposited on the fiber surface, which can effectively improve the mechanical strength and conductivity of the positive electrode material, so that the material maintains stability during long-term cycle use and reduces capacity attenuation.
[0031] 2. The present invention extracts natural shellac to obtain a shellac extract, and then mixes the extract with 1,8-naphthalene dicarboxylic anhydride and ethanol, heats the mixture, and then performs ultrasonic dispersion to obtain a derivative carbon precursor solution. The cationic colloid solution is dried and pre-sintered, and then the obtained sintered powder is crushed. The sintered powder is immersed in the derivative carbon precursor solution, and then directly dried and sintered at a high temperature to obtain a derivative carbon-coated positive electrode material. In the process of preparing the derivative carbon precursor solution, the shellac extract containing functional groups such as esters, phenols, and carboxyl groups forms a cross-linked carbon precursor with 1,8-naphthalene dicarboxylic anhydride, which has the following properties during the high-temperature treatment process: The aromatic structure of 1,8-naphthalene dicarboxylic anhydride easily forms a planar conjugated carbon structure, improves the graphitization degree of the carbon layer, is beneficial to the rapid conduction of electrons in the carbon layer, and improves the discharge specific capacity of the positive electrode material. The oxygen-containing groups in the shellac extract are partially retained on the surface of the carbon layer after sintering, which can increase the interface interaction between the carbon layer and the positive electrode material, improve the bonding force of the carbon layer and the overall stability of the positive electrode material. After sintering, the uniform conductive coating layer synergistically formed by the two can not only enhance the electronic conductivity of the positive electrode material and improve the discharge specific capacity of the battery, but also has good interface stability, thereby improving the cycle stability of the positive electrode material.
[0032] 3. The present invention obtains a complexing agent by uniformly stirring diphenyl phosphite, tartaric acid and anhydrous ethanol. During the complexing process, the phosphite group and the hydroxyl and carboxyl groups in the tartaric acid simultaneously participate in the coordination of metal ions, which can improve the coordination saturation and stability of the metal ions, forming a synergistic complexing system, which can capture the metal ions escaped by electrospinning, form a uniform and tight lattice structure in the material, and thus improve the cycle performance of the material.
[0033] 4. The present invention introduces aluminum at the lithium position and uses niobium with a 5d electronic structure to replace transition metal ions, thereby exerting the synergistic effect of aluminum / niobium to improve the cycle stability of lithium-rich layered materials. In addition, the introduction of aluminum and niobium can increase the electronic conductivity of the system. These changes can also improve the rate performance of lithium-rich layered materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a flow chart of the method for preparing the aluminum-niobium co-doped lithium-rich layered positive electrode material used in an embodiment of the present invention. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1: An aluminum-niobium co-doped lithium-rich layered positive electrode material and a preparation method thereof, such as Figure 1 As shown, the following steps are included:
[0037] S1: Preparation of cationic colloid solution
[0038] S1.1: Mix soluble manganese sulfate, nickel sulfate, cobalt sulfate and aluminum sulfate to obtain a mixed metal salt, wherein the molar ratio of manganese, nickel, cobalt and aluminum elements in the mixed metal salt is 4.15:1:1:0.1, dissolve the mixed metal salt in 15 times the mass of deionized water, then add ethylene glycol 4 times the mass of the mixed metal salt, and stir at a speed of 300 rpm for 20 minutes to obtain solution A;
[0039] S1.2: polyvinyl pyrrolidone and anhydrous ethanol are mixed in a container at a mass ratio of 1:10, and then stirred at a speed of 600 rpm for 25 minutes to obtain a PVP solution. Two portions of the PVP solution are placed in a container, and one portion of solution A is slowly added dropwise while stirring at a speed of 450 rpm. When the addition of solution A is completed, stirring is stopped to obtain a spinning solution;
[0040] S1.3: Diphenyl phosphite, tartaric acid and anhydrous ethanol are mixed in a container at a mass ratio of 1:3:15, and stirred at a speed of 300 rpm for 10 minutes to obtain a complexing agent. Lithium acetate, complexing agent and deionized water are mixed evenly at a mass ratio of 1:10:45 to obtain solution B. The alkaline solution is placed in a container, and an electrospinning machine is installed above the container. The distance between the syringe of the electrospinning machine and the liquid surface of the alkaline solution is 20 cm. The spinning solution is placed in the syringe of the electrospinning machine, and the syringe hole is The diameter of the electrospinning solution was 600 μm, the spinning voltage was set to 8 kV, the spinning temperature was set to 30 °C, the syringe injection speed was set to 0.1 mm / min, and then the electrospinning machine was started to electrospin the spinning solution and continuously sprayed into the alkaline solution. At the same time, solution B was slowly added, and the solution was continuously stirred at a speed of 350 rpm and heated to 55 °C. The pH of the alkaline solution was kept unchanged. After the electrospinning was completed, solution C was obtained. The proportions of lithium ions, manganese ions, nickel ions, cobalt ions and aluminum ions in solution C were calculated according to Li 1.15 Al 0.05 (Mn 0.54 Ni 0.13 Co 0.13 ) 0.78 Nb 0.02 The mixture was mixed with water in a stoichiometric ratio of 1% O2 and then heated in a water bath at 80°C for 3 hours to obtain a cationic colloid solution.
[0041] S2: Preparation of Derivatized Carbon Precursor Solution
[0042] S2.1: crush the natural shellac and pass it through a 40-mesh sieve to obtain shellac powder, mix the shellac powder and hexane in a mass ratio of 1:25, place it in a constant temperature ultrasonic water bath, adjust the power to 200 W, and the temperature to 40°C, perform ultrasonic treatment for 20 minutes, and then filter and collect the solid to obtain dewaxed shellac;
[0043] S2.2: Mix dewaxed shellac and anhydrous ethanol in a mass ratio of 1:20 in a container, heat to 50°C, and stir at a speed of 400 rpm for 40 minutes, then filter to remove insoluble impurities to obtain a shellac extract, evaporate and concentrate the shellac extract to 1 / 4 of the original volume, then add deionized water of the same volume as the reduced volume, stir evenly, place in a refrigerator at 3°C for 8 hours, then centrifuge at a centrifugal speed of 3800 rpm for 10 minutes, filter to retain the precipitate, and then dry at 45°C to obtain a shellac extract;
[0044] S2.3: Place the shellac extract, 1,8-naphthalene dicarboxylic anhydride and ethanol in a mass ratio of 1:0.1:8 in an ultrasonic disperser, heat to 50°C, then ultrasonically disperse at an ultrasonic frequency of 15 kHz for 12 minutes, and cool to room temperature to obtain a derivative carbon precursor solution.
[0045] S3: Coating and sintering of positive electrode powder materials
[0046] S3.1: Place the cationic colloid solution obtained in step S1.3 in a container, and according to the ratio of lithium ions, manganese ions, nickel ions, cobalt ions and aluminum ions in solution C of step S1.3, 1.15 Al 0.05 (Mn 0.54 Ni 0.13 Co 0.13 ) 0.78 Nb 0.02 The niobium pentachloride powder was added in a stoichiometric ratio of 1.5% to 1.5% O2, stirred at a speed of 600 rpm for 20 minutes, then dried in an oven at a temperature of 150° C. for 10 hours, and then pre-sintered in a tube furnace at a temperature of 450° C. for 6 hours. After cooling, the powder was crushed in an ultrafine grinder to a particle size of 10 μm to obtain a sintered powder.
[0047] S3.2: Immerse the sintered powder obtained in step S3.1 in the derived carbon precursor solution, stir at a rotation speed of 300 rpm for 15 minutes, and then place the derived carbon precursor solution in an oven at a temperature of 75°C to dry it to obtain a solid product. Fill the solid product into a crucible and place it in a tubular furnace. Under a N2 protective atmosphere, heat it to 750°C at a heating rate of 3°C / min, maintain the temperature and calcine for 10 hours to obtain an aluminum-niobium co-doped lithium-rich layered positive electrode material.
[0048] Example 2: An aluminum-niobium co-doped lithium-rich layered positive electrode material and a preparation method thereof, such as Figure 1 As shown, the following steps are included:
[0049] S1: Preparation of cationic colloid solution
[0050] S1.1: Mix soluble manganese nitrate, nickel nitrate, cobalt nitrate and aluminum nitrate to obtain a mixed metal salt, wherein the molar ratio of manganese, nickel, cobalt and aluminum elements in the mixed metal salt is 4.15:1:1:1.1, dissolve the mixed metal salt in 15 times the mass of deionized water, then add ethylene glycol 6 times the mass of the mixed metal salt, and stir at a rotation speed of 300 rpm for 20 minutes to obtain solution A;
[0051] S1.2: polyvinyl pyrrolidone and anhydrous ethanol are mixed in a container at a mass ratio of 1:10, and then stirred at a speed of 600 rpm for 25 minutes to obtain a PVP solution. Three parts of the PVP solution are placed in a container, and 1.5 parts of solution A are slowly added dropwise while stirring at a speed of 450 rpm. After the addition of solution A is completed, stirring is stopped to obtain a spinning solution;
[0052] S1.3: Diphenyl phosphite, tartaric acid and anhydrous ethanol are mixed in a container at a mass ratio of 1:4:20, and stirred at a speed of 300 rpm for 10 minutes to obtain a complexing agent. Lithium nitrate, complexing agent and deionized water are mixed evenly at a mass ratio of 1:20:60 to obtain solution B. The alkaline solution is placed in a container, and an electrospinning machine is installed above the container. The distance between the syringe of the electrospinning machine and the liquid surface of the alkaline solution is 20 cm. The spinning solution is placed in the syringe of the electrospinning machine, and the syringe hole is The diameter of the electrospinning solution was 600 μm, the spinning voltage was set to 8 kV, the spinning temperature was set to 30 °C, the syringe injection speed was set to 0.1 mm / min, and then the electrospinning machine was started to electrospin the spinning solution and continuously sprayed into the alkaline solution. At the same time, solution B was slowly added, and the solution was continuously stirred at a speed of 350 rpm and heated to 55 °C. The pH of the alkaline solution was kept unchanged. After the electrospinning was completed, solution C was obtained. The proportions of lithium ions, manganese ions, nickel ions, cobalt ions and aluminum ions in solution C were calculated according to Li 1.05 Al 0.15 (Mn 0.54 Ni 0.13 Co 0.13 ) 0.78 Nb 0.02 The mixture is mixed with water in a stoichiometric ratio of O2 and then heated in a water bath at 80°C for 3 hours to obtain a cationic colloid solution.
[0053] S2: Preparation of Derivatized Carbon Precursor Solution
[0054] S2.1: crush the natural shellac and pass it through a 40-mesh sieve to obtain shellac powder, mix the shellac powder and hexane in a mass ratio of 1:30, place it in a constant temperature ultrasonic water bath, adjust the power to 200 W, and the temperature to 40°C, perform ultrasonic treatment for 20 minutes, and then filter and collect the solid to obtain dewaxed shellac;
[0055] S2.2: Mix dewaxed shellac and anhydrous ethanol in a mass ratio of 1:25 in a container, heat to 50°C, and stir at a speed of 400 rpm for 40 minutes, then filter to remove insoluble impurities to obtain a shellac extract, evaporate and concentrate the shellac extract to 1 / 4 of the original volume, then add deionized water of the same volume as the reduced volume, stir evenly, place in a refrigerator at 3°C for 8 hours, then centrifuge at a centrifugal speed of 3800 rpm for 10 minutes, filter to retain the precipitate, and then dry at 45°C to obtain a shellac extract;
[0056] S2.3: Place the shellac extract, 1,8-naphthalene dicarboxylic anhydride and ethanol in a mass ratio of 1:0.2:10 in an ultrasonic disperser, heat to 50°C, then ultrasonically disperse at an ultrasonic frequency of 15 kHz for 12 minutes, and cool to room temperature to obtain a derivative carbon precursor solution.
[0057] S3: Coating and sintering of positive electrode powder materials
[0058] S3.1: Place the cationic colloid solution obtained in step S1.3 in a container, and according to the ratio of lithium ions, manganese ions, nickel ions, cobalt ions and aluminum ions in solution C of step S1.3, 1.05 Al 0.15 (Mn 0.54 Ni 0.13 Co 0.13 ) 0.71 Nb 0.09 The niobium pentachloride powder was added in a stoichiometric ratio of 1.5% to 1.5% O2, stirred at a speed of 600 rpm for 20 minutes, then dried in an oven at a temperature of 150° C. for 10 hours, and then pre-sintered in a tube furnace at a temperature of 450° C. for 6 hours. After cooling, the powder was crushed in an ultrafine grinder to a particle size of 10 μm to obtain a sintered powder.
[0059] S3.2: Immerse the sintered powder obtained in step S3.1 in the derived carbon precursor solution, stir at a rotation speed of 300 rpm for 15 minutes, and then place the derived carbon precursor solution in an oven at a temperature of 75°C to dry it to obtain a solid product. Fill the solid product into a crucible and place it in a tubular furnace. Under a N2 protective atmosphere, heat it to 750°C at a heating rate of 3°C / min, maintain the temperature and calcine for 10 hours to obtain an aluminum-niobium co-doped lithium-rich layered positive electrode material.
[0060] Example 3: An aluminum-niobium co-doped lithium-rich layered positive electrode material and a preparation method thereof, such as Figure 1 As shown, the following steps are included:
[0061] S1: Preparation of cationic colloid solution
[0062] S1.1: Mix soluble manganese chloride, nickel chloride, cobalt acetate and lithium acetate evenly to obtain a mixed metal salt, wherein the molar ratio of manganese, nickel, cobalt and aluminum elements in the mixed metal salt is 4.15:1:1:0.1, dissolve the mixed metal salt in 20 times the mass of deionized water, then add ethylene glycol 4 times the mass of the mixed metal salt, and stir at a speed of 400 rpm for 25 minutes to obtain solution A;
[0063] S1.2: polyvinyl pyrrolidone and anhydrous ethanol are mixed in a container at a mass ratio of 1:12, and then stirred at a speed of 800 rpm for 30 minutes to obtain a PVP solution. Two portions of the PVP solution are placed in a container, and one portion of solution A is slowly added dropwise while stirring at a speed of 500 rpm. After the addition of solution A is completed, stirring is stopped to obtain a spinning solution;
[0064] S1.3: Diphenyl phosphite, tartaric acid and anhydrous ethanol are mixed in a container at a mass ratio of 1:3:15, and stirred at a speed of 500 rpm for 15 minutes to obtain a complexing agent. Lithium acetate, complexing agent and deionized water are mixed evenly at a mass ratio of 1:10:45 to obtain solution B. The alkaline solution is placed in a container, and an electrospinning machine is installed above the container. The distance between the syringe of the electrospinning machine and the liquid surface of the alkaline solution is 30 cm. The spinning solution is placed in the syringe of the electrospinning machine, and the syringe hole is The diameter of the electrospinning solution was 800 μm, the spinning voltage was set to 10 kV, the spinning temperature was set to 35 °C, the syringe push speed was set to 0.3 mm / min, and then the electrospinning machine was started to electrospin the spinning solution and continuously sprayed into the alkaline solution. At the same time, solution B was slowly added, and the solution was continuously stirred at a speed of 400 rpm and heated to 60 °C. The pH of the alkaline solution was kept unchanged. After the electrospinning was completed, solution C was obtained. The ratio of lithium ions, manganese ions, nickel ions, cobalt ions and aluminum ions in solution C was determined according to Li 1.15 Al 0.05 (Mn 0.54 Ni 0.13 Co 0.13 ) 0.71 Nb 0.09 The mixture is mixed with water in a stoichiometric ratio of O2 and then heated in a water bath at 90°C for 4 hours to obtain a cationic colloid solution.
[0065] S2: Preparation of Derivatized Carbon Precursor Solution
[0066] S2.1: natural lac is crushed and passed through a 50-mesh sieve to obtain lac powder, the lac powder and hexane are mixed in a mass ratio of 1:25 and placed in a constant temperature ultrasonic water bath, the power is adjusted to 250 W, the temperature is adjusted to 45°C, and ultrasonic treatment is performed for 30 minutes, and then the solid is collected by filtration to obtain dewaxed lac;
[0067] S2.2: Mix dewaxed shellac and anhydrous ethanol in a mass ratio of 1:20 in a container, heat to 60°C, and stir at a speed of 500 rpm for 45 minutes, then filter to remove insoluble impurities to obtain a shellac extract, evaporate and concentrate the shellac extract to 1 / 3 of the original volume, then add deionized water of the same volume as the reduced volume, stir evenly, place in a refrigerator at 4°C for 10 hours, then centrifuge at a centrifugal speed of 4000 rpm for 15 minutes, filter to retain the precipitate, and then dry at 50°C to obtain a shellac extract;
[0068] S2.3: Place the shellac extract, 1,8-naphthalene dicarboxylic anhydride and ethanol in a mass ratio of 1:0.1:8 in an ultrasonic disperser, heat to 55°C, then ultrasonically disperse at an ultrasonic frequency of 20 kHz for 16 minutes, and cool to room temperature to obtain a derivative carbon precursor solution.
[0069] S3: Coating and sintering of positive electrode powder materials
[0070] S3.1: Place the cationic colloid solution obtained in step S1.3 in a container, and according to the ratio of lithium ions, manganese ions, nickel ions, cobalt ions and aluminum ions in solution C of step S1.3, 1.15 Al 0.05 (Mn 0.54 Ni 0.13 Co 0.13 ) 0.78 Nb 0.02 The niobium pentachloride powder was added in a stoichiometric ratio of 1.5% to 1.5% O2, stirred at a speed of 800 rpm for 25 minutes, then dried in an oven at a temperature of 200°C for 12 hours, and then pre-sintered in a tube furnace at a temperature of 500°C for 8 hours. After cooling, the niobium pentachloride powder was crushed in an ultrafine grinder to a particle size of 20 μm to obtain a sintered powder.
[0071] S3.2: Immerse the sintered powder obtained in step S3.1 in the derived carbon precursor solution, stir at a speed of 400 rpm for 20 minutes, and then place the derived carbon precursor solution in an oven at a temperature of 80°C to dry it to obtain a solid product. Fill the solid product into a crucible and place it in a tubular furnace. Under a N2 protective atmosphere, heat it to 8850°C at a heating rate of 5°C / min, maintain the temperature and calcine for 8 hours to obtain an aluminum-niobium co-doped lithium-rich layered positive electrode material.
[0072] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 removes step S1.2 and does not perform electrospinning in step S1.3. Instead, solution A and solution B are mixed and then ammonia water is added to adjust the pH to 8. The remaining steps are the same as in Example 1 to obtain a positive electrode material, which is recorded as Comparative Example 1.
[0073] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that step S2 is removed in Comparative Example 2, and the sintered powder is not immersed in the derived carbon precursor solution in step S3.2. The remaining steps are the same as in Example 1 to prepare a positive electrode material, which is recorded as Comparative Example 2.
[0074] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 removes step S2.1 and step S2.2, and does not add shellac extract in step S2.3. The remaining steps are the same as those in Example 1 to prepare a positive electrode material, which is recorded as Comparative Example 3.
[0075] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that, in Comparative Example 4, 1,8-naphthalene dicarboxylic anhydride is not added in step S2.3, and the remaining steps are the same as those in Example 1 to prepare a positive electrode material, which is recorded as Comparative Example 4.
[0076] Comparative Example 5: The difference between Comparative Example 5 and Example 1 is that, in Comparative Example 5, the complexing agent is not prepared in step S1.3, and the subsequent complexing agent is replaced by anhydrous citric acid. The remaining steps are the same as Example 1 to obtain a positive electrode material, which is recorded as Comparative Example 5.
[0077] Preparation of the battery: Take the aluminum-niobium co-doped lithium-rich layered positive electrode material prepared in Examples 1-3 and Comparative Examples 1-5, mix them with carbon black and polyvinylidene fluoride in a mass ratio of 8:1:1, stir and grind them in a grinder, and then mix them with an appropriate amount of N-methyl-2-pyrrolidone (NMP) to form a uniform mixed solution. Then, the mixture is coated on an aluminum foil with a thickness of about 10 mm (excluding the thickness of the blank aluminum foil), and quickly placed in an oven at 80°C for 12 hours. After compacting with a roller, each positive electrode is cut. The diameter of each aluminum foil is 14 mm, and the mass of the positive electrode material on each aluminum foil is about 3.0 mg. The battery is assembled in an argon-filled glove box (H2O and O2 are both <0.1 ppm), and a mixed solution of 1MLiPF6 EC, EMC and DMC (volume ratio of 1:1:1) is used as the electrolyte, Celgard2400 is used as the separator, and metal Li is used as the negative electrode to prepare a battery sample.
[0078] Experiment 1: Battery samples were tested under different conditions using a Neware battery test system (CT4008Tn-5V10mA164, Shenzhen, China) at 0.1C, 0.2C, 1C, 2C, 5C, 10C and 0.1CmAg -1 The rate performance was tested at the current density, as shown in Table 1, where 1C = 160mAg -1 , and the cycle performance was tested at 0.5C, as shown in Table 2.
[0079] It can be seen from Table 1 and Table 2 that the rate performance and cycle performance of the battery samples prepared in Examples 1-3 are greater than those of the battery samples prepared in Comparative Examples 1-5, which proves that the spinning solution is directly sprayed into the alkaline solution by an electrospinning machine and the addition of solution B can greatly improve the rate performance and cycle performance of the material, and the chelating agent prepared by mixing diphenyl phosphite, tartaric acid and anhydrous ethanol can also improve the cycle performance of the material to a certain extent. It can be seen from Comparative Examples 2-4 that the sum of the performance degradation of Comparative Example 2 + Comparative Example 3 is greater than the performance degradation of Comparative Example 4, which proves that the shellac extract and 1,8-naphthalene dicarboxylic anhydride have a synergistic effect and can improve the discharge specific capacity and cycle stability of the material.
[0080] Table 1: Discharge capacity of battery samples at different rates
[0081]
[0082] Table 2: Cycling performance of battery samples
[0083]
[0084] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. An aluminum-niobium co-doped lithium-rich layered positive electrode material, characterized in that: The chemical formula of the positive electrode material is: Li 1.2-x Al x (Mn 0.54 Ni 0.13 Co 0.13 ) 0.8-y Nb y O2, of which 0.01 <x<0.1,0.01<y<0.1; The preparation method comprises the following steps: S1: Preparation of cationic colloid solution Mix manganese salt, nickel salt, cobalt salt and aluminum salt evenly and dissolve them in deionized water. Then add ethylene glycol and stir evenly to obtain solution A. Mix polyvinylpyrrolidone and absolute ethanol evenly to obtain a PVP solution. Slowly drip solution A into the PVP solution while stirring to obtain a spinning solution. Stir diphenyl phosphite, tartaric acid and absolute ethanol evenly to obtain a complexing agent. Mix soluble lithium salt, complexing agent and deionized water evenly to obtain solution B. Spray the spinning solution into an alkaline solution through an electrospinning machine, and slowly add solution B at the same time to keep the pH unchanged. Continuously heat and stir the alkaline solution during the spinning process to obtain solution C. The ratio of lithium ions, manganese ions, nickel ions, cobalt ions and aluminum ions in solution C is in the stoichiometric ratio of Li 1.2-x Al x (Mn 0.54 Ni 0.13 Co 0.13 ) 0.8-y Nb y O2, with 0.01 < x < 0.1 and 0.01 < y < 0.
1. Then carry out water bath heating to obtain a cationic colloidal solution; S2: Preparation of Derivatized Carbon Precursor Solution The natural shellac is crushed and mixed with hexane for constant temperature ultrasonic treatment, and the solid is collected by filtration to obtain dewaxed shellac, the dewaxed shellac is mixed with anhydrous ethanol, and the mixture is heated and stirred, and the shellac extract is obtained by filtration, the shellac extract is concentrated and evaporated, and then deionized water is added, and the mixture is stirred evenly and refrigerated, and then centrifuged and filtered, and the precipitate is retained and dried to obtain a shellac extract, and the shellac extract, 1,8-naphthalene dicarboxylic anhydride and ethanol are mixed, heated, ultrasonically dispersed, and cooled to obtain a derivative carbon precursor solution; S3: Coating and sintering of positive electrode powder materials Place the cationic colloidal solution in a container. According to the ratios of lithium ions, manganese ions, nickel ions, cobalt ions, and aluminum ions in solution C, add niobium salt powder in a stoichiometric ratio of Li 1.2-x Al x (Mn 0.54 Ni 0.13 Co 0.13 ) 0.8-y Nb y O2, where 0.01 < x < 0.1 and 0.01 < y < 0.
1. After stirring evenly, dry it, then place it in a tubular furnace for pre-sintering. After cooling and pulverizing, obtain the sintered powder. Immerse the sintered powder in the derivative carbon precursor solution, stir, and then dry the derivative carbon precursor solution to obtain a solid product. Place the solid product in a tubular furnace and calcine it under a N2 protective atmosphere to obtain the aluminum-niobium co-doped lithium-rich layered cathode material.
2. The aluminum-niobium co-doped lithium-rich layered positive electrode material according to claim 1, characterized in that: The preparation method of the present invention comprises the following steps: S1.1: Mix soluble manganese salt, nickel salt, cobalt salt and aluminum salt to obtain a mixed metal salt, wherein the molar ratio of manganese, nickel, cobalt and aluminum elements in the mixed metal salt is 4.15:1:1:(0.1-1.1), dissolve the mixed metal salt in 15-20 times the mass of deionized water, then add 4-6 times the mass of ethylene glycol of the mixed metal salt, and stir at a speed of 300-400 rpm for 20-25 minutes to obtain solution A; S1.2: polyvinyl pyrrolidone and anhydrous ethanol are mixed in a container at a mass ratio of 1: (10-12), and then stirred at a speed of 600-800 rpm for 25-30 minutes to obtain a PVP solution, 2-3 portions of the PVP solution are placed in a container, 1-1.5 portions of solution A are slowly added dropwise, and stirring is performed at a speed of 450-500 rpm. When the addition of solution A is completed, stirring is stopped to obtain a spinning solution; S1.3: Mix diphenyl phosphite, tartaric acid and absolute ethanol in a mass ratio of 1:(3 - 4):(15 - 20) in a container, stir at a speed of 300 - 500 rpm for 10 - 15 minutes to obtain a complexing agent. Mix the soluble lithium salt, the complexing agent and deionized water evenly in a mass ratio of 1:(10 - 20):(45 - 60) to obtain solution B. Place the alkaline solution in a container, with an electrospinning machine installed above the container. The syringe of the electrospinning machine is 20 - 30 cm away from the liquid surface of the alkaline solution. Place the spinning solution in the syringe of the electrospinning machine, with the syringe aperture being 600 - 800 μm. Set the electrospinning voltage to 8 - 10 kV, the electrospinning temperature to 30 - 35 °C, and the syringe injection speed to 0.1 - 0.3 mm / min. Then start the electrospinning machine to electrospin the spinning solution and continuously spray it into the alkaline solution, while slowly adding solution B, continuously stir at a speed of 350 - 400 rpm and heat to 55 - 60 °C to keep the pH of the alkaline solution unchanged. After the electrospinning ends, obtain solution C. The ratio of lithium ions, manganese ions, nickel ions, cobalt ions and aluminum ions in solution C is formulated according to the stoichiometric ratio of Li 1.2-x Al x (Mn 0.54 Ni 0.13 Co 0.13 ) 0.8-y Nb y O2, where 0.01 < x < 0.1 and 0.01 < y < 0.
1. Then carry out a water bath heating at 80 - 90 °C for 3 - 4 hours to obtain a cationic colloidal solution.
3. The aluminum-niobium co-doped lithium-rich layered positive electrode material according to claim 1, characterized in that: The preparation method of the present invention comprises the following steps: S2.1: crush the natural shellac and pass it through a 40-50 mesh sieve to obtain shellac powder, mix the shellac powder and hexane in a mass ratio of 1:(25-30) and place it in a constant temperature ultrasonic water bath, adjust the power to 200-250W, the temperature to 40-45℃, perform ultrasonic treatment for 20-30 minutes, and then filter and collect the solid to obtain dewaxed shellac; S2.2: Mix dewaxed shellac and anhydrous ethanol in a mass ratio of 1:(20-25) in a container, heat to 50-60°C, and stir at a speed of 400-500rpm for 40-45 minutes, then filter to remove insoluble impurities to obtain a shellac extract, evaporate and concentrate the shellac extract to 1 / 4-1 / 3 of the original volume, then add deionized water of the same volume as the reduced volume, stir evenly, place in a refrigerator at 3-4°C for 8-10 hours, then centrifuge at a centrifugal speed of 3800-4000rpm for 10-15 minutes, filter to retain the precipitate, and then dry at 45-50°C to obtain a shellac extract; S2.3: Place shellac extract, 1,8-naphthalene dicarboxylic anhydride and ethanol in a mass ratio of 1: (0.1-0.2): (8-10) in an ultrasonic disperser, heat to 50-55°C, then ultrasonically disperse at an ultrasonic frequency of 15-20 kHz for 12-16 minutes, and cool to room temperature to obtain a derivative carbon precursor solution.
4. The aluminum-niobium co-doped lithium-rich layered positive electrode material according to claim 1, characterized in that: The preparation method of the present invention comprises the following steps: S3.1: Place the cationic colloidal solution prepared in step S1.3 in a container. According to the ratios of lithium ions, manganese ions, nickel ions, cobalt ions, and aluminum ions in solution C in step S1.3, add niobium salt powder in the stoichiometric ratio of Li 1.2-x Al x (Mn 0.54 Ni 0.13 Co 0.13 ) 0.8-y Nb y O2, where 0.01 < x < 0.1 and 0.01 < y < 0.
1. Stir at a speed of 600 - 800 rpm for 20 - 25 minutes, then place it in an oven and dry at a temperature of 150 - 200 °C for 10 - 12 hours. Then place it in a tube furnace and pre-sinter at a temperature of 450 - 500 °C for 6 - 8 hours. After cooling, place it in an ultrafine grinder and pulverize to obtain sintered powder; S3.2: Immerse the sintered powder obtained in step S3.1 in the derived carbon precursor solution, stir at a speed of 300-400rpm for 15-20 minutes, and then place it in an oven to dry the derived carbon precursor solution at a temperature of 75-80℃ to obtain a solid product. Fill the solid product into a crucible and put it into a tubular furnace. Under a N2 protective atmosphere, heat it to 750-850℃ at a heating rate of 3-5℃ / min, maintain the temperature and calcine for 8-10 hours to obtain an aluminum-niobium co-doped lithium-rich layered positive electrode material.
5. The method for preparing an aluminum-niobium co-doped lithium-rich layered positive electrode material according to claim 2, characterized in that: In step S1.1, the manganese salt is one or more of manganese sulfate, manganese nitrate and manganese chloride; the nickel salt is one or more of nickel sulfate, nickel nitrate and nickel chloride; the cobalt salt is one or more of cobalt sulfate, cobalt nitrate and cobalt acetate; the aluminum salt is one or more of aluminum sulfate, aluminum nitrate and aluminum chloride.
6. The method for preparing an aluminum-niobium co-doped lithium-rich layered positive electrode material according to claim 2, characterized in that: The soluble lithium salt in step S1.3 is one or both of lithium nitrate and lithium acetate.
7. The method for preparing an aluminum-niobium co-doped lithium-rich layered positive electrode material according to claim 2, characterized in that: The alkaline solution in step S1.3 is an ammonia solution with a pH of 8.5-9, and the volume is 10-15 times the volume of the subsequent spinning solution.
8. The method for preparing an aluminum-niobium co-doped lithium-rich layered positive electrode material according to claim 4, characterized in that: The niobium salt powder in step S3.1 is niobium pentachloride powder.
9. The method for preparing an aluminum-niobium co-doped lithium-rich layered positive electrode material according to claim 4, characterized in that: The particle size of the sintered powder in step S3.1 is 10-20 μm.
Citation Information
Patent Citations
Lithium-rich manganese-based positive electrode material
CN116706049A